Kenya Toward a National Crop and Livestock Insurance Program : Summary of Policy Suggestions - World Bank Group (World Bank, Washington, DC, 2016)
At the request of the government of Kenya and under its guidance, a team of national and international experts conducted an appraisal of different agricultural insurance options for Kenya.This appraisal, as set out in this document and the accompanying technical analysis, lays out the costs and benefits of developing large-scale agricultural insurance that involves both the public and private spheres.The analysis considers potential structures for large-scale agricultural insurance in Kenya, the fiscal cost to the government of Kenya, and the economic benefits for farmers and pastoralists. In order for it to partner with the private sector to prepare and implement a large scale agricultural insurance program, the government should consider taking the following next steps.The government of Kenya may build on there commendations by the Program Steering Committee to take the lead in formulating a national policy on agriculture insurance, in cooperation with county administrations and private insurance companies. The government of Kenya may develop a road map for establishing the institutions required for large-scale agricultural insurance programs, with the goal of covering at least a fifth of Kenya’s agricultural producers. As next steps for establishing livestock insurance, the government of Kenya may decide how to integrate the proposed insurance product with other existing protection mechanisms. As next steps for crop insurance, the government of Kenya may seek consultations with agricultural banks and work with private sector insurers to develop a data audit system acceptable to international reinsurers.